Common Endothelial Nitric Oxide Synthase Single Nucleotide Polymorphisms are not Related With the Risk for Restless Legs Syndrome - Jiménez-Jiménez, Félix Javier; Agúndez, Blanca G.; Gómez-Tabales, Javier; Alonso-Navarro, Hortensia; Turpín-Fenoll, Laura; Millán-Pascual, Jorge; Díez-Fairén, Mónica; Álvarez, Ignacio; Pastor, Pau; Calleja, Marisol; García-Ruiz, Rafael; Navarro-Muñoz, Santiago; et al. (Frontiers in Pharmacology, 2021)
Because nitric oxide and endothelial dysfunction could play a role in the pathogenesis of idiopathic restless legs syndrome (RLS), as was suggested by some preliminary data, we investigated the possible association between the rs2070744 variants in the endothelial nitric oxide synthase (eNOS or NOS3) gene (chromosome 7q36.1) and the risk for RLS in a Caucasian Spanish population. We assessed the frequencies of NOS3 single nucleotide polymorphisms (SNPs) rs2070744, rs1799983, and rs79467411 genotypes and allelic variants in 273 patients with idiopathic RLS and 325 healthy controls using a TaqMan-based qPCR assay. We also analyzed the possible influence of genotype frequency on age at onset of RLS symptoms, gender, family history of RLS, and response to drugs commonly used in the treatment of RLS such as dopaminergic drugs, clonazepam, and GABAergic drugs. The frequencies of genotypes and allelic variants were not associated with the risk for RLS and were not influenced by gender, age, and positive family history of RLS. We identified weak statistical associations of the SNP rs1799983 with the response to dopamine agonists (Pc = 0.018 for the rs1799983 G/T genotype) and of the SNP rs79467411 with the response to clonazepam (Pc = 0.018 for the rs79467411 G allele), although these findings should be cautiously interpreted and require further confirmation. These associations aside, our findings suggest that common NOS3 SNPs are not associated with the risk for idiopathic RLS in Caucasian Spanish people.